Stress and muscular dystrophy: a genetic screen for dystroglycan and dystrophin interactors in Drosophila identifies cellular stress response components. - Kucherenko, M.M.; Marrone, A.K.; Rishko, V.M.; Magliarelli, H.F.; Shcherbata, H.R. (Developmental Biology, 2011)
In Drosophila, like in humans, Dystrophin Glycoprotein Complex (DGC) deficiencies cause a life span shortening disease, associated with muscle dysfunction. We performed the first in vivo genetic interaction screen in ageing dystrophic muscles and identified genes that have not been shown before to have a role in the development of muscular dystrophy and interact with dystrophin and/or dystroglycan. Mutations in many of the found interacting genes cause age-dependent morphological and heat-induced physiological defects in muscles, suggesting their importance in the tissue. Majority of them is phylogenetically conserved and implicated in human disorders, mainly tumors and myopathies. Functionally they can be divided into three main categories: proteins involved in communication between muscle and neuron, and interestingly, in mechanical and cellular stress response pathways. Our data show that stress induces muscle degeneration and accelerates age-dependent muscular dystrophy. Dystrophic muscles are already compromised; and as a consequence they are less adaptive and more sensitive to energetic stress and to changes in the ambient temperature. However, only dystroglycan, but not dystrophin deficiency causes extreme myodegeneration induced by energetic stress suggesting that dystroglycan might be a component of the low-energy pathway and act as a transducer of energetic stress in normal and dystrophic muscles.